Sugar import and metabolism during seed development - Weber, Hans; Borisjuk, Ljudmilla; Wobus, Ulrich (Trends in plant science, 1997)
During seed development, cell division is followed by elongation, differentiation and storage. In legumes, this sequence of events has been found to spread in a wave-like manner, creating a developmental gradient across the cotyledons. All these processes, including storage activities, appear to be subject to metabolic control. Sucrose is imported during seed development, and a sucrose breakdown pathway mediated by cell wall invertase operates in the seed coat during early development. The resulting high hexose state is associated with growth and mitotic activity. The storage/maturation phase is initiated following the developmentally controlled loss of invertase, and is accompanied by the formation of an active sucrose transport system. Invertases are therefore regarded as a control element in the changing carbohydrate status of seeds, and the invertase control hypothesis for seed development has emerged. Cotyledonary sucrose metabolism is controlled by a cycle of synthesis and breakdown involving sucrose-phosphate synthase and sucrose synthase, respectively; net breakdown for storage product synthesis involves sucrose synthase. The complex framework of interactions involved in these pathways is now being elucidated via a combination of biochemical, physiological and molecular methods.